Primary culture of human amniotic fluid cells harvested from full-term pregnancies - Joharry , Muhammad Khair; Karuppiah, Thilakavathy; Rejali, Zulida; Yazid, Mohd Nazri; Nordin, Norshariza (Tissue Engineering and Regenerative Medicine Society of Malaysia, 2014)
Heterogeneous cells contained in human amniotic fluid (AF) are believed to hold therapeutic potential. Mid-term AF has been discovered to harbor high potency stem cell population. However, it is not clear whether AF of full-term pregnancy contains this type of cells. In an effort to explore this possibility, primary culture of AF harvested from full-term pregnancies or during deliveries needs to be established. Here, we aimed to culture and propagate AF cells of 38-40 weeks gestation collected during normal (ARM) and cesarean section (C-Sect) deliveries. The time taken for both cells to reach confluency and the cell morphology were compared and evaluated. We found C-Sect samples took shorter time to confluent compared to ARM samples in Amniomax with both exhibiting similar cell morphology. These results prove the presence of viability cells residing in full-term AF, thus, giving us high hope for the existence of stem cell population in the fluid, which is normally discarded.